2018
DOI: 10.1111/plb.12895
|View full text |Cite
|
Sign up to set email alerts
|

GhSTOP1, a C2H2 type zinc finger transcription factor is essential for aluminum and proton stress tolerance and lateral root initiation in cotton

Abstract: The Aluminum (Al) and proton (H ) ions are major acid soil stress factors deleteriously affecting plant root growth and crop yield. In our preliminary studies, cotton seedlings (Gossypium hirsutum L.) displayed very sensitive phenotypes to Al and H rhizotoxicities. Based on previous Arabidopsis results, we aimed to characterize the Al stress responsive Sensitive to Proton rhizotoxicity 1 (GhSTOP1) transcription system in cotton by RNAi mediated down-regulation. With the help of seed embryo apex explants, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 73 publications
0
24
0
1
Order By: Relevance
“…Many previous studies reported that most of C2H2-ZFPs function as transcription factors and play important roles in plant growth and development [23,36,37,40,76]. Our subcellular localization prediction showed that 92% of B .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Many previous studies reported that most of C2H2-ZFPs function as transcription factors and play important roles in plant growth and development [23,36,37,40,76]. Our subcellular localization prediction showed that 92% of B .…”
Section: Discussionmentioning
confidence: 73%
“…SIZF3 can significantly increase the level of AsA and enhance salt stress tolerance [35], GhSTOP1 can accelerate root growth and is essential for aluminum and proton stress tolerance in A . thaliana [36]. SGR5 is involved in primary events of geotropism in inflorescence stems in A .…”
Section: Introductionmentioning
confidence: 99%
“…In rice, the C2H2-ZFPs play a role in many aspects of stress tolerance, regulating the responses to cold, drought, oxidative, and salt stresses (Huang et al, 2009; Sun et al, 2010; Xu et al, 2008; Zhang et al, 2014). The functions of the C2H2-ZFPs in many other plants have also been reported, and are often found to be involved in plant development processes such as morphogenesis of cell and trichomes, ripening and senescence (Chang et al, 2018; Moreau et al, 2018; Weng et al, 2015), and stress resistance such as aluminum, drought and salt (Atreyee et al, 2018; Li et al, 2018; Rai, Singh & Shah, 2012). These findings showed that the C2H2-ZFPs are active in multiple physiological processes under stress conditions; however, the functions of the majority of the C2H2-ZFPs in tomato have not been reported.…”
Section: Introductionmentioning
confidence: 98%
“…The phenotypes in response to Al stress were also consistent with other C2H2 ZFPs in different species. For instance, GhSTOP1 could improve Al and H + stress tolerance in transgenic cotton plants, and it played a role as an essential gene to regulate the expression of several genes that are necessary for the tolerance mechanisms in acid aluminum soil and lateral root development [46]. In addition, STOP1-like proteins were indicated to associate with Al tolerance in sweet sorghum.…”
Section: Discussionmentioning
confidence: 99%